On the measurement of long-run income inequality. Empirical evidence from Norway, 1875-2013 - Rolf Aaberge; Anthony B Atkinson; Jørgen Modalsli (Statistics Norway, Research Department, 2016)
In seeking to understand inequality today, a great deal can be learned from history. However, there are few countries for which the long-run development of income inequality has been charted. Many countries have records of incomes, taxes and social support. This paper presents a new methodology constructing income inequality indices from such tabular data. The methodology is applied to Norway, for which rich historical data sources exist covering the period 1875 to 2013. Taking careful account of the definition of income and population and the availability of micro data starting in 1967, an upper and lower bound for the pre-tax income Gini coefficient for core households is produced. Our findings cast doubt on the idea that Norway in the nineteenth century was an egalitarian society, supporting the view of de Tocqueville that the young United States exhibited less inequality than the states of Europe. We show that overall inequality of gross family incomes is lower today than a hundred years ago. At the same time, there has not been a consistent downward trend over time in inequality; rather, the fall in inequality took place in a series of episodes. Comparison to existing data for Denmark and the United States reveals remarkable commonalities, as well as distinct periods of difference. This supports the view that the evolution of income inequality is best studied, not in terms of an over-arching theory, but by studying episodes of rising and falling inequality, and the manifold forces in operation
Keywords: D31; D63; N33; N34; 330; income; inequality; distribution; Norway; long-run changes